MicroRNA-Mediated Responses to Chromium Stress Provide Insight Into Tolerance Characteristics of Miscanthus sinensis - Nie, Gang; Liao, Zongchao; Zhong, Minyi; Zhou, Jie; Cai, Jiabang; Liu, Aiyu; Wang, Xia; Zhang, Xinquan (Frontiers in Plant Science, 2021)
Chromium (Cr) is a heavy metal in nature, which poses a potential risk to toxicity to both animals and plants when releasing into the environment. However, the regulation of microRNA (miRNA)-mediated response to heavy metal Cr has not been studied in Miscanthus sinensis. In this study, based on high-throughput miRNA sequencing, a total of 104 conserved miRNAs and 158 nonconserved miRNAs were identified. Among them, there were 45 differentially expressed miRNAs in roots and 13 differentially expressed miRNAs in leaves. The hierarchical clustering analysis showed that these miRNAs were preferentially expressed in a certain tissue. There were 833 differentially expressed target genes of 45 miRNAs in roots and 280 differentially expressed target genes of 13 miRNA in leaves. After expression trend analysis, five significantly enriched modules were obtained in roots, and three significantly enriched trend blocks in leaves. Based on the candidate gene annotation and gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) function analysis, miR167a, novel_miR15, and novel_miR22 and their targets were potentially involved in Cr transportation and chelation. Besides, miR156a, miR164, miR396d, and novel_miR155 were identified as participating in the physiological and biochemical metabolisms and the detoxification of Cr of plants. The results demonstrated the critical role of miRNA-mediated responses to Cr treatment in M. sinensis, which involves ion uptake, transport, accumulation, and tolerance characteristics.